An Analysis of the Social Interaction Disorder Concept - Vivi Sovianti; Meidiana Dwidiyanti; Dian Yuli Wijayanti (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Social interaction disorder is a condition where a person does not have a good interaction with others, society, and the environment. This will affect the cognitive, affective, and psychomotor aspects of the patient. Feelings that arise afterward will negatively impact and endanger the patient. The purpose of this literature is to clarify the concept of social interaction. Analysis of the concept of social interaction using the Walker and Avants method. This method uses an eight-step approach to conceptual analysis of social interaction. The concepts identified are 1) concept selection; 2) determine the purpose or objective of the analysis; 3) identify all concepts used; 4) define the attributes that define the concept; 5) create a case model; 6) forming a boundary line; 7) identify antecedents and consequences; and 8) define empirical references. The concept analysis of social interaction consist antecedent, attributes, and consequences. The antecedents of social interaction disorder is caused by low self-esteem, excessive anxiety, assuming that interact with others is not important, feeling useless, being alone and unpleasant experiences. The attributes of social interaction. Social isolation can be structurally described as disrupted social interaction, lack of contact and loss of relations with other people, family, friends or even the environment. For positive social interactions, we found that people who experience social interaction disorders prefer to have a relationship with someone who is considered worthy of interaction. Social isolation can cause disruption of social interaction. The negative effects caused are loneliness, depression, hallucinations and suicide.